Analysis of the Braking Process for Curvilinear Motion of Vehicle - FUNDOWICZ, Piotr; SAR, Hubert; BRUKALSKI, Mateusz; ABRAMOWSKI, Michał (Engineering Transactions, 2025)
Road incident reconstruction frequently includes the possibility of avoiding a collision. To perform such analysis, it is necessary to compare the available distance with the minimum braking distance. Therefore, to avoid a collision, the braking distance must be shorter than the available distance. The braking distance depends on parameters such as tyre-to-road adhesion coefficient, the initial velocity of a vehicle, the driver’s reaction time and the time needed to reach full braking force. However, the problem is that, in practice, none of these values are known during traffic incident reconstruction. As a result, the estimated vehicle velocity is uncertain. This is due to the method used to reconstruct a road incident (and the errors in the evidence data). The tyre-to-road adhesion coefficient depends on many factors and can be estimated with limited accuracy, usually ±0.1. The uncertainty of the estimate is approximately ±15%. The reaction time of a specific driver under the conditions present during a road incident is not precisely known. Therefore, an average value for most drivers is taken into account. It is assumed that a healthy driver’s reaction time should not exceed this value, and a longer reaction time is associated with incorrect driving behavior. The time taken to reach full braking force in a real situation is also unknown. Usually, average values are taken from the literature, without the analysis of a technical condition of a vehicle. This article considers the mechanics of vehicle braking, taking into account the action of lateral forces on this vehicle while considering a curved track. The maximum deceleration during braking is determined analytically, and a condition is formulated to indicate whether it is justified to use an advanced computational model instead of the basic one described in the literature. The analysis includes some dimensionless parameters describing the position of the center of gravity, tangential forces between the tyre and the road, the intensity of turning and braking, suspension characteristics, and asymmetrical mass distribution. This dimensionless approach may be useful for applying the presented analysis of braking on the road arc in accident reconstruction, especially when comparative analysis is recommended.